Tingkat Keberhasilan Penetasan Telur Penyu Hijau (Chelonia Mydas, Linnaeus 1758) di Pantai Sebubus, Kabupaten Sambas - Irwan Lovadi, Sheavtiyan, Tri Rima Setyawati, (Jurnal Protobiont, 2014)
A succeed hatchery of green turtles eggs is determined by the condition of the environment and the position of the nests. The purposes of this research are to find out the succeed hatchery level of green turtle and the environmental condition of the nest in Sebubus coastal area. The sample of the nest was randomly selected and taken based on the existing nest proportion. There were three parameters, namely hatchability, physical characters of the coast and environmental conditions surrounding the nest. There were 24 nests in Sungai Belacan coast, 21 in Munggu Resak and three nests in Tanjung Kemuning. The number of eggs range between 85 102 eggs per nest. The percentage of green turtles hatchery in Sebubus coast were varied from 87.69% - 93.13%. 75% of the nests were found under pandanus tree. The shaded nests showed a higher hatchery percentage of 86.64% - 95.6%. The slope of Sebubus coast was ranged from 40 4.820. Temperature of nest incubation was varied from 28.180C to 28.370C. Green turtles dominantly made their nest in sandy substrate. The pH level of the observed nests was categorized as not too acidic ranging from 5.74 to 6.16. The overall environmental condition in Sebubus coastal area supports the hatchery of green turtles eggs.